HUBUNGAN ANTARA PEMAKAIAN ALAT KONTRASEPSI SUNTIK DENGAN GANGGUAN MENSTRUASI PADA AKSEPTOR KB SUNTIK - Andi St. Umrah; Andi Kasrida Dahlan (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2016)
The purpose of this study was to determine the relationship between the use of the injectable contraceptive menstrual disorders in family planning acceptors syringes in health centers-Bone Bone North Luw.This type of research is quantitative research with cross sectional. The sample in this study are acceptor injections that come to visit at the time of the study in Health Center Bone-bone North Luwu in 2015 as many as 41 people with purposive sampling techniques.The results showed there is a relationship between the use of injectable contraceptive with menstrual disorders on injecting kb acceptor- Health Center Bone Bone North Luwu in 2015, where the value of p = 0.000 <value α: 0:05.For midwives who work in the health center Bone-bone further improve the coverage of family planning acceptors and counseling about the side effects of injections on the acceptors. For acceptors are expected to choose appropriate contraception. Keywords : Contraceptive Injections, Menstrual Disorders